ABOUT INFORMATION AND COMMUNICATION TECHNOLOGIES FURTHER DEVELOPMENT IN HIGHER EDUCATION SYSTEM - S. О. Voinova; M. T. Stepanov (Автоматизация технологических и бизнес-процессов, 2025)
Abstract. At the end of the 20th century, humanity created an information society characterized by the rapid development of information and communication technologies. Providing the higher education system with the theory and practice of developing and using these technologies is aimed at achieving the goals of education and upbringing in higher education. The Law of Ukraine "About National Informatization Program" demonstrates the relevance of the issue. The purpose of the study is a comprehensive study of the ways of further development of information and communication technologies in the higher education system. There is a growing need for a personally oriented, creative, competitive educator with an information culture, capable of designing and filling the information educational environment of Ukraine created on the basis of Internet technologies. Students should be provided with conditions for searching and obtaining information, developing cognitive and communicative abilities, etc. It is important to ensure the quality of accessible education and increase the availability of quality education. It is necessary to develop principles for the implementation of information and telecommunication technologies that improve the quality and expand access to education, deepen the capabilities of existing traditional teaching technologies, and connect scientists, educators, and students with effective resources within the virtual educational space. Successful improvement of higher education based on information and communication technologies will contribute to improving the quality and accessibility of education, integrating the national education system into the scientific, industrial, social, public, and cultural information infrastructure of the world community.